Paciente femenino de 50 años de edad con síndrome de inmunodeficiencia adquirida - Manjarrez Gaibor, Arianna Noellia (2018)
Acquired immunodeficiency syndrome is a syndrome that encompasses various pathologies that manifest as a result of the alteration caused by the infection of the human immunodeficiency virus (HIV). HIV penetrates inside the cells and can remain inactive for long periods of time, and sometimes multiplies and can destroy cells of the immune system, and thus the body loses the ability to respond to various opportunistic infections. Maintain an adequate nutritional status, to favor the functioning of the immune system. A 50-year-old patient came to the hospital due to dizziness and shortness of breath, the patient reported that she was a sex worker and 10 years ago she was diagnosed with the human immunodeficiency virus, her family medical history indicates that her father is diabetic, has received antiretroviral treatment (ART) during the 10 years. Eating habits were modified the same as the patient accepted. The aim of the nutritional treatment was to improve the nutritional status. It is estimated to reduce weight loss and achieve an adequate nutritional status along with diet and medication and thus achieve normal glucose values. Finalizing this case study concludes that the human immunodeficiency virus is a disease that is progressing little by little therefore the retroviral treatment must follow it throughout life together with a good diet. The nutritional status of the patient is improved by means of anthropometric parameters, an increase in weight of 3kg is evidenced in three months